ESTIMATION OF NOISE INFLUENCE ON THE WORKERS IN FOUNDRY - A. M. Lazarenkov; S. A. Horeva; V. V. Melnichenko (Литьë и металлургия)
Estimation of vibration influence of the workers in foundry is given. The results of investigation of vibration levels of the used foundry equipment and tool instrument are given.